The “Instrumentality” Heuristic - Labroo, Aparna A.; Kim, Sara (Psychological Science, 2009)
The literature overwhelmingly demonstrates that feelings of ease are good and that objects that are easy to process are much liked. We propose, and demonstrate across three experiments, that this is not the case when people are pursuing a goal. This is because people pursuing a goal (e.g., “become kinder”) usually invest efforts in whichever means (e.g., donate to a particular charity) they perceive as most instrumental for attaining their goal. Consequently, in their minds there is a correspondence between instrumentality of a means and feelings of effort. This correspondence becomes reversed in people's minds during goal pursuit, and they also come to view an object that is associated with feelings of effort rather than ease as more instrumental for goal attainment and consequently more desirable. When an object is not a means to fulfill an accessible goal, or when goals relating to the means are not accessible, subjective feelings of ease improve evaluation, as found in previous research on ease of processing.